Interviewing and diagnostic exercises for clinical and counseling skills building - Berman, Pearl, 1955- (New York, NY : Routledge, 2024)
"This text is specifically designed to meet the needs of those teaching and learning interviewing and diagnostic skills in clinical, counselling, and school psychology, counselor education, licensed clinical social workers and other programs preparing mental health professionals. It offers a rich array of practical, hands-on, class and workshop tested role-playing and didactic exercises. The profiles included throughout provide students/trainees with a wealth of information about each client's feelings, thoughts, actions, and relationship patterns on which to draw as they proceed through the different phases of the initial interview, one playing the client and one the interviewer. Each client profile is followed by exercises which highlight attending, asking open and closed questions, engaging in reflective listening, responding to nonverbal behavior, making empathetic comments, summarizing, redirecting, supportively confronting, and commenting on process. This second edition is based on the new diagnostic system (DSM 5-TR) and all profiles and case examples are updated. Throughout, the author emphasizes the importance of understanding diversity and respecting the client's perceptions, and of reflecting on the ways in which the interviewer's own identity influences both the process of interviewing and that of diagnosis. This text is essential for both students and practitioners of clinical psychology, counselling, psychiatry, nursing, social work, and other allied professions"--
Keywords: Mental health counseling -- Problems, exercises, etc; Psychotherapy -- Problems, exercises, etc; Clinical competence; PSYCHOLOGY / Psychotherapy / General